2018
DOI: 10.1007/s00018-018-2846-4
|View full text |Cite
|
Sign up to set email alerts
|

The adhesion receptor GPR56 is activated by extracellular matrix collagen III to improve β-cell function

Abstract: AimsG-protein coupled receptor 56 (GPR56) is the most abundant islet-expressed G-protein coupled receptor, suggesting a potential role in islet function. This study evaluated islet expression of GPR56 and its endogenous ligand collagen III, and their effects on β-cell function.MethodsGPR56 and collagen III expression in mouse and human pancreas sections was determined by fluorescence immunohistochemistry. Effects of collagen III on β-cell proliferation, apoptosis, intracellular calcium ([Ca2+]i) and insulin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 52 publications
6
47
0
Order By: Relevance
“…The functional significance of the ECM in normal islet function is well reported. Thus, ECM proteins are involved in a wide range of functions such as protecting -cells from apoptosis, enhancing insulin secretion, -cell migration and adhesion, and they play a role in pancreas development (Davis et al, 2012;Kaido et al, 2004;Huang et al, 2011;Shih et al, 2016;Arzouni et al, 2017;Llacua et al, 2018;Olaniru et al, 2018a).…”
Section: The Extracellular Matrix and -Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional significance of the ECM in normal islet function is well reported. Thus, ECM proteins are involved in a wide range of functions such as protecting -cells from apoptosis, enhancing insulin secretion, -cell migration and adhesion, and they play a role in pancreas development (Davis et al, 2012;Kaido et al, 2004;Huang et al, 2011;Shih et al, 2016;Arzouni et al, 2017;Llacua et al, 2018;Olaniru et al, 2018a).…”
Section: The Extracellular Matrix and -Cell Functionmentioning
confidence: 99%
“…insulin secretion and protects them from apoptosis, in a GPR56-dependent manner (Dunér et al, 2016;Olaniru, et al, 2018a), demonstrating that islets use -cell-expressed GPR56 to sense signals from ECM collagen III to improve -cell mass and secretory function. Consistent with this, islets in which GPR56 expression was acutely downregulated with siRNA had less insulin content and reduced insulin secretory capacity (Dunér et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Another interesting member of the aGPCR family is GPR56. It is the most abundant islet GPCR [44], and it is expressed exclusively by the β-cells in islets [5]. Activation of islet GPR56 by its endogenous ligand, collagen III, has beneficial effects, including potentiation of glucose-stimulated insulin secretion and protection of islets against the deleterious effects of inflammation that occur in diabetes [5,47].…”
Section: Adhesion Gpcrsmentioning
confidence: 99%
“…It is the most abundant islet GPCR [44], and it is expressed exclusively by the β-cells in islets [5]. Activation of islet GPR56 by its endogenous ligand, collagen III, has beneficial effects, including potentiation of glucose-stimulated insulin secretion and protection of islets against the deleterious effects of inflammation that occur in diabetes [5,47]. Moreover, a recent study has shown that pre-treating human islets with mesenchymal stromal cell-derived ECM, which is rich in the GPR56 agonist collagen III, led to enhanced insulin output [2].…”
Section: Adhesion Gpcrsmentioning
confidence: 99%
See 1 more Smart Citation